Methylation Levels of CADM1, MAL, and MIR124-2 in Cervical Scrapes for Triage of HIV-Infected, High-Risk HPV-Positive Women in Kenya. (1st November 2015) - De Vuyst, Hugo; Franceschi, Silvia; Plummer, Martyn; Mugo, Nelly R.; Sakr, Samah R.; Meijer, Chris J. L. M.; Heideman, Daniëlle A. M.; Tenet, Vanessa; Snijders, Peter J. F.; Hesselink, Albertus T.; Chung, Michael H.
Abstract : Objectives: To evaluate the value of cervical cell methylation markers in screening HIV-infected women also positive for high-risk human papillomavirus (hrHPV). Design: Cross-sectional and prospective. Methods: Two hundred forty-eight HIV-infected hrHPV-positive women enrolled in a cervical cancer screening study in Nairobi, Kenya, had colposcopy-directed biopsy and histological diagnoses. Exfoliated cervical cells were used to measure methylation levels of the CADM1, MAL, and MIR124-2 genes using quantitative methylation-specific polymerase chain reaction. Methylation levels were summarized as cycle threshold (Ct) ratios compared with the β-actin gene. Median Ct ratios were compared across histological diagnoses, with 95% confidence intervals calculated by bootstrapping. Methylation levels at 6 months were assessed in 128 women who remained hrHPV positive. Results: All 3 methylation markers showed significantly ( P < 0.001) raised median Ct ratios in women with cervical intraepithelial neoplasia (CIN) grade 3 compared with women with a normal cervix. When markers were combined into a single test, the area under the receiver operating characteristic curve for prediction of CIN2 or worse (CIN2+) was 0.80. When the test was calibrated to have similar specificity, sensitivity of the combined tri-marker test for CIN2+ was comparable with cytology [atypical squamous cells of undetermined significance or worse] (89% and 95%, respectively) and superior to visual inspection with acetic acid (85% vs 70%) and HPV16/18 genotyping (65% vs 40%). Among women with no CIN2+ at baseline and persistent hrHPV at 6-month follow-up, MAL-m1 and MIR124-2 Ct ratios increased significantly. Conclusions: Methylation markers in combination with HPV testing may offer a full molecular screening strategy to the many HIV-infected women who are also hrHPV positive. Abstract : Supplemental Digital Content Is Available in the Text.